Molecular identification of streptomyces spp. isolated from agricultural soil at Puncak Alam, Kuala Selangor, Malaysia / Fatimah Zahrah Mustaffa - Mustaffa, Fatimah Zahrah (2015)
Soil in ecological field was widely used for study and Actinomycetes, mainly Streptomycetes, were exist in these environments and a good sources of bioactive metabulites‘ This genus was Gram-positive bacteria with filaments in branches, ubiquitous, aerobic, soil-like odour, and high G+C content, The aims of this study were to isolate Streptomyces spp, from the agricultural soil in Puncak Alam, Kuala Selangor, Malaysia‘ The isolates were examined for morphological characteristics, antimicrobial activity and genus confin-natiun. Soil samples were pre-heated and cultured aerobically on ISP-Z agar for 14 days at 37 °C. Primary screenings of the isolates for antimicrobial activity were conducted by using cross streak method against Bacillus sub/ilis, Bacillus cereus, Salmonella typhimurium, Staphylococcus aureus and Escherichia coli. DNA of the isolates was extracted using boiling method and 168 rDNA gene was amplified by PCR for genus continuation. A total of four isolates of Streptomyces spp‘ were identified based on colour of the aerial mycelium showed as grey, yellow, brown and white. Isolate with brown colour groups, C4 displayed moderate inhibition against Bacillus subtilis, Bacillus cereus, and Staphylococcus aureus. No inhibition of C4 against Gram negative bacteria. Two isolates, Cl (yellow group) and C5 (orange group) showed weak inhibition against Bacillus subtilis and Bacillus cereus. Whereas, no inhibition of all bacteria tested for grey group isolated namely, C3. DNA fragment with 520 bp of the amplified 165 rDNA gene were observed on the Agarose gel. The blast sequenced of Cl isolate was identified as Streptomyces davawensis JCM 4913, Streptomyces pratensis ATCC 33331, and Streptomyces griseus subsp‘ griseus NBRC 13350 DNA with 99% similarity. C3 isolate also have 99 % similarity with Streptomyces albus J 1074 and Streptomyces coelicolor A3 (2) Meanwhile, C4 isolate was identical to Streptomyces bingchenggenxis BCW-I and Slreplomyces cattleya str, NRRL 8057 with similarity of 98%. C5 isolate has 99 % similarity with Streptomyces collinus Tu 365 and Streptomyces roseochromogenus subsp, oscitans. As a conclusion, the presence of the Streptomyces spp‘ was identified from this soil and has significant antimicrobial activities against tested bacteria